PENGARUH PRICE DISCOUNT, SALES FORCE CAPABILITY DAN STORE ATMOSPHERE TERHADAP IMPULSE BUYING PADA KONSUMEN HALAL MART HNI HPAI BC SEMARANG - Wa Ode Sitti Nurrahmah; M Roby Jatmiko (Anindyaguna Ekonobisnis : Jurnal Ekonomi dan Bisnis STIE Anindyaguna, 2021)
This study aims to examine the effect of Price Discount, Sales Force Capability and Store Atmosphere on Impulse Buying at the Halal Mart HNI-HPAI BC Semarang consumers. This study uses primary data, the method of collecting data using questionnaires. The sample collection of 110 respondents in this study used a non probability sampling method. The analysis used in this study included Test Validity, Reliability Test, Classical Assumption Test, Multiple Linear Regression Analysis, and Hypothesis Testing. The results of analysis using multiple linear regression can be seen that the Price Discount variable does not significantly influence the Impulse Buying on consumers of Halal Mart HNI HPAI BC Semarang. Sales Force Capability has a positive and significant effect on Impulse Buying on Halal Mart HNI-HPAI BC Semarang consumers and Store Atmosphere has a positive and significant effect on Impulse Buying at Halal Mart HNI-HPAI BC Semarang consumers. The results of the analysis using the t test can be seen that Price Discount has no significant effect while, Sales Force Capability and Store Atmosphere have a significant effect on Impulse Buying on consumers of Halal Mart HNI-HPAI BC Semarang.